Freer markets, more rules : regulatory reform in advanced industrial countries - Vogel, Steven Kent. 4 0 16; 5 (Ithaca, N.Y. : Cornell University Press, 1996)
Over the past fifteen years, the United States, Western Europe, and Japan have transformed the relationship between governments and corporations. The changes are complex and the terms used to describe them often obscure the reality. In Freer Markets, More Rules, Steven K. Vogel dispenses with euphemisms and makes sense of this recent transformation.;In defiance of conventional wisdom, Vogel contends that the deregulation revolution of the 1980s and 1990s never happened. The advanced industrial countries moved toward liberalization or freer markets at the same time that they imposed reregulation or more rules. Moreover, the countries involved did not converge in regulatory practice but combined liberalization and reregulation in markedly different ways. The state itself, far more than private interest groups, drove the process of regulatory reform. Thus, the story of deregulation is one rich in paradox: a movement aimed at reducing regulation increased it; a movement propelled by global forces reinforced national differences; and a movement that purported to reduce state power was led by the state itself.;Vogel's astute and far-reaching analysis compares deregulation in Britain and Japan, with special attention to the telecommunication and financial services industries. He also considers such important sectors as broadcasting, transportation, and utilities in the United States, France, and Germany.
Introduction: The Deregulation Revolution That Wasn't -- 1. Understanding Regulatory Reform -- 2. Why Change the Rules? -- 3. The United Kingdom and Japan: Two Paths to Regulatory Reform -- 4. Telecommunications: The Creation of Competition -- 5. Financial Services: The Big Bang and the Proliferation of Rules -- 6. Regulatory Reform British Style: The Separation of Regulatory Powers -- 7. Telecommunications: Reregulation with a Vengeance -- 8. Financial Services: The Ministry of Finance and the Perpetual Bargain -- 9. Regulatory Reform Japanese Style: The Strategy Behind Slowness -- 10. Other Countries: The Many Roads to Reregulation -- 11. The Irony of State-Led Deregulation.
Includes bibliographical references and index.
Keywords: 2 -- 0; 6; Deregulation;Trade regulation;Deregulation;Trade regulation -- Great Britain;Great Britain;Japan;Japan -- 20 -- Case studies.;Case studies.;Case studies.;Case studies; 20; Economic conditions;Policies;Of;Government.;Great Britain.;Japan.; Case studies